Penerapan Teori Keperawatan Comfort Katharine Kolcaba dalam Pemberian Asuhan Keperawatan Perioperatif - Zulkifli B. Pomalango (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
The use of Kolcaba's theory of comfort is easy to apply in the perioperative field and is useful for addressing a variety of patient comfort needs. Fulfillment of holistic comfort through indicators of relief (freedom), ease (calmness), transcendence (happiness). This literature review was carried out by collecting articles and textbooks from databases such as Proquest, Scient Direct, Google Search, Google Scholar. The search was carried out using the keywords